Angki Purbandono dalam Karya Material Ethics: Narasi Kecil dan Estetika Seni Penjara - Aghara, Qanissa (JURNAL RUPA, 2023)
This research artcle illustrates the artwork creaton of Angki Purbandono’s “Material Ethics” a series that was made during his tme in jail on 2012. Angki Purbandono is a renowned Indonesian artst that actvely partcipated in the Indonesian contemporary art scene since 1999. He is famous for implementng scanography technique for photography artworks, including “Material Ethics” series. This research is an interdisciplinary descriptve qualitatve research, in the realm of art and social studies. Literature reviews and interviews were included as methods in data gathering. This research will be based on the theories of postmodernism, especially Lyotard’s noton of narratve, and Carceral Aesthetcs theory. In conclusion, this research shows that “Material Ethics” series shows postmodernism tendencies through the implementaton of bricolage technique. It also enhances the noton of small narratves that was iterated by Lyotard. From the perspectve of Carceral Aesthetcs, this artwork shows the tendency of carceral memories.